Multicenter evaluation of a synthetic single-crystal diamond detector for CyberKnife small field size output factors. Issue 4 (April 2016) - Russo, Serenella; Masi, Laura; Francescon, Paolo; Frassanito, Maria Cristina; Fumagalli, Maria Luisa; Marinelli, Marco; Falco, Maria Daniela; Martinotti, Anna Stefania; Pimpinella, Maria; Reggiori, Giacomo; Verona Rinati, Gianluca; Vigorito, Sabrina; et al.
Abstract : Highlights: First CyberKnife multicenter study on fixed cones and on Iris™ collimators. MicroDiamond uncorrected vs MC corrected silicon diode output factors. For CyberKnife output factor PTW60019 can be considered near "correction free". Abstract: Purpose: The aim of the present work was to evaluate small field size output factors (OFs) using the latest diamond detector commercially available, PTW-60019 microDiamond, over different CyberKnife systems. OFs were measured also by silicon detectors routinely used by each center, considered as reference. Methods: Five Italian CyberKnife centers performed OFs measurements for field sizes ranging from 5 to 60 mm, defined by fixed circular collimators (5 centers) and by Iris ™ variable aperture collimator (4 centers). Setup conditions were: 80 cm source to detector distance, and 1.5 cm depth in water. To speed up measurements two diamond detectors were used and their equivalence was evaluated. MonteCarlo (MC) correction factors for silicon detectors were used for comparing the OF measurements. Results: Considering OFs values averaged over all centers, diamond data resulted lower than uncorrected silicon diode ones. The agreement between diamond and MC corrected silicon values was within 0.6% for all fixed circular collimators. Relative differences between microDiamond and MC corrected silicon diodes data for Iris ™ collimator were lower than 1.0% for all apertures in the totality of centers. The two microDiamond detectors showed similar characteristics, in agreement with the technical specifications. Conclusions: Excellent agreement between microDiamond and MC corrected silicon diode detectors OFs was obtained for both collimation systems fixed cones and Iris ™, demonstrating the microDiamond could be a suitable detector for CyberKnife commissioning and routine checks. These results obtained in five centers suggest that for CyberKnife systems microDiamond can be used without corrections even at the smallest field size.